Hak Dan Kewajiban Para Pihak Dalam Menjaga Rahasia Dagang Franchise - Alkautsar Raga Trenggono; Budi Ispriyarso (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractThere are many franchise businesses, one of which was researched in this writing is the